Using GPUs to Enable Simulation with Computational Gravitational Dynamics in Astrophysics. - Zwart, Simon Portegies; Bedorf, Jeroen (Computer (00189162), 2015)
Optimizations for individual N-body techniques allow the simulation of collisonal or collisionless systems, but not both together. Hybrid code running on GPUs meets this requirement, and enabled the efficient and accurate simulation of 11 interacting galaxies with a massive black hole in each of their nuclei.